Synthesis and properties of Pb(Co1/3Nb2/3)O3 ceramics - Unruan M. (2014)
In this study, Pb(Co1/3Nb2/3)O3 or PCN ceramics have been produced by sintering PCN powders synthesized from lead oxide (PbO) and cobalt niobate (CoNb2O6) with an effective method developed for minimizing the level of PbO loss during sintering. Attention has been focused on relationships between sintering conditions, phase formation, density, microstructural development, dielectric and ferroelectric properties of the sintered ceramics. The densities of sintered PCN ceramics increased with increasing sintering temperature. However, it was observed that at too high temperature the density began to decrease. Change of dielectric properties with sintering temperature also followed the same trend as the density. Based on X-ray diffraction analysis, density data, SEM micrograph, and dielectric properties, the optimum sintering temperature for a high purity PCN ceramic was found to be about 1100 and 1150 °C. A strongly diffused dielectric peak also showed a typical characteristic of ferroelectric relaxors. The P-E hysteresis loops observed at -70 °C were of slim-loop type with small remnant polarization values, which confirmed relaxor ferroelectric behavior of PCN ceramics. © 2007 Elsevier B.V. All rights reserved.